Penggunaan Metode Audi Lingual Dalam Meningkatkan Kemampuan Berbicara Peserta Didik dalam Bahasa Jepang - Afis Alhadi; Jehwae, Phaosan (Journal of Information System and Education Development, 2023)
The abstract should be in full reasoned italics at the beginning of the paper, with a single column like this, below the author information. Use the word "Abstract" as the title in 10-dot tenses, bold, to the left of the column, initially capitalized. The abstract must be 9-point, single line type, up to 200 words, and contain three to six keywords related to the articles. The abstract should contain the background of the research, the goals of the research, the methods used and the results obtained.